2010
DOI: 10.1007/s11104-010-0682-x
|View full text |Cite
|
Sign up to set email alerts
|

Pleiotropy of pea RisfixC supernodulation mutation is symbiosis-independent

Abstract: Mutations affecting the development of root symbiosis between legume plants (Fabaceae) and nodule bacteria (rhizobia) are often associated with pleiotropy. This might either primarily be caused by the mutation or develops as a physiological consequence of a changed nodule structure, number and activity. Three pleiotropic traits were revealed in the pea (Pisum sativum L.) mutant RisfixC which is of supernodulation/nitrate-tolerant symbiosis (Nts) type. They comprise shortened internodes, reduced shoot dry mass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Indeed, there is usually a trade-off for C use between roots and nodules to reach an optimal equilibrium between benefits related to SNF and C cost for nodule formation and functioning without impairing root development (Hacin et al, 1997;Tricot et al, 1997). In some cases, such as in hypernodulating mutants for which the autoregulation of the nodulation is disrupted (see the review from Mortier et al, 2012), many pleiotropic effects including shoot growth and yield depression have been reported (Novak et al, 2011). Our data suggest that a finely tuned nodule number initiation during the post-stress period is critical to ensure optimal N nutrition without excessive C costs (case of Kayanne), leading to plant growth recovery and contributing the N pool available for remobilization to the seeds later on during the reproductive period (Zeiher et al, 1982;Schiltz et al, 2005).…”
Section: Contrasted Strategies Between Genotypes During the Re-waterimentioning
confidence: 99%
“…Indeed, there is usually a trade-off for C use between roots and nodules to reach an optimal equilibrium between benefits related to SNF and C cost for nodule formation and functioning without impairing root development (Hacin et al, 1997;Tricot et al, 1997). In some cases, such as in hypernodulating mutants for which the autoregulation of the nodulation is disrupted (see the review from Mortier et al, 2012), many pleiotropic effects including shoot growth and yield depression have been reported (Novak et al, 2011). Our data suggest that a finely tuned nodule number initiation during the post-stress period is critical to ensure optimal N nutrition without excessive C costs (case of Kayanne), leading to plant growth recovery and contributing the N pool available for remobilization to the seeds later on during the reproductive period (Zeiher et al, 1982;Schiltz et al, 2005).…”
Section: Contrasted Strategies Between Genotypes During the Re-waterimentioning
confidence: 99%
“…Nevertheless, only sparse information is available on the impact of hypernodulation on nitrogen nutrition in relation with carbon nutrition traits. In a few studies, hypernodulation was associated with higher N content in root tissues (Day et al 1986;Novak et al 2011), in the shoot (Novak et al 2011 and references therein) or in harvested seeds ), but this was not related to carbon nutrition traits. In other studies, hypernodulation was associated to lower specific N 2 fixing activity of nodules (in g N 2 fixed per g nodule) and high N status as compared to wild type , without full characterisation of carbon nutrition traits.…”
Section: Introductionmentioning
confidence: 98%
“…Hence, most studies on hypernodulating mutants have reported negative pleiotropic traits related to carbon nutrition such as depressed shoot growth, shortened internodes or fasciation of the stem, and reduction of roots development and growth (e.g., pea : Postma et al 1988;Duc and Messager 1989;Sagan and Duc 1996;Krusell et al 2002;Bourion et al 2007; soybean: Matsunami et al 2004;Voisin et al 2013). These pleiotropic effects might be a direct effect of the mutated gene on those carbon nutrition traits, or it may result from a physiological consequence of deregulated (and therefore excessive) nodule number (Novak et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Albeit without ultimate proof, these nodulation-related CLE peptides have been hypothesized to act as the Q signal to activate the CLV-like receptor complex in the shoot for AON. In addition to the CLE peptides, several mutants have been identified that might be affected in genes involved in the control of AON in the root, such as nod3, rdn1, rdh1, tml, and plenty (Postma et al, 1988;Ishikawa et al, 2008;Magori et al, 2009;Novák, 2010;Yoshida et al, 2010;Novák et al, 2011;Schnabel et al, 2011). These mutants might be defective in the genes that control the root-derived signals or the root-to-shoot processing/transducing signals or vice versa (Li et al, 2009;Novák, 2010).…”
mentioning
confidence: 99%